DICTION (IN ARAB SATELLITE CHANNELS) A SIGNAL SYSTEM : (study of written And oral patterns) - Reza Mubarak, muhamad (ALBAHITH ALALAMI, 2008)
Communication has seen a big advancement through ages; concepts, procedures and technologies, it has also seen a similar advancement of language. What unites language and media is the fact that each one of them guides and contributes to the other; media exists and results from language and from the other sign systems, and what strengthens this connection is the symbolic language system, as media helps it by providing knowledge and information. The change that occurred through time must leave a significant trace in the media, for example Diction, which has changed concerning development and growth, also the ways and mediums of media have become manifold and widespread. This change affected the recipient whether it was a reader, listener or watcher; as diction became no longer read in written paragraphs where punctuation rules are respected, it neither became a representation of the meaning in an attempt to be described, but it is rather another picture represented with words and performance, along with a deep knowledge of the language’s characteristics, especially oral characteristics, As do appear the personal and phonetic features of maintaining signaling systems: word system, sentence system, text system, speech system. The modern science of language has encouraged the responsables of communication to make use of the tremendous achievements of our times since the beginning of the 20th century, especially in the development of semiotics, which became sign of this century’s development. Whilst, Linguistics is trying to summarize the special minor signifying units from the sentence. Semiotics occupies a decent position, as it aims to extrapolate the semantic system according to a unit larger than the sentence, that is the speech from which there is no benefit simply by just adding the minor signifying units that construct it. However, it is extracted